Monitoring Hemoglobin Levels and Consumption of Iron Supplement in Adolescent Girls Cigandamekar Subdistrict Kuningan Regency - Nova Oktavia; Haty Latifah Priatni; Rina Nurhayatina; Nourma Nurjanah (Jurnal Pengabdian, 2025)
Anemia is often experienced by Adolescent Girls. As early detection and to be aware of the occurrence of anemia, it is best for Adolescent Girls to have their hemoglobin levels checked. Providing iron supplements to Adolescent Girls is very important because this program is useful for preventing anemia. The purpose of this activity is to monitor hemoglobin levels and iron supplements consumption in Adolescent Girls at school. This Activity was carried out in January 2024 in the Madrasah Tsanawiyah and the Senior High School. The materials and tools used for the smooth running of this activity include rapid hemoglobin tests, lancet needles, alcohol cotton, hemoglobin sticks, and iron supplements. This activity consists of several stages, namely preparation, implementation and evaluation stages. Results of monitoring Hemoglobin levels in 2023-2024, There is an increase in the number of targets undergoing Hemoglobin level examinations. There was a significant decrease in the number of MTs students who experienced anemia. There is an increase in the number of Senior high school students who experience anemia in the mild, moderate and severe. All MTs and Senior High School Students get iron supplements. After mentoring and education, the students drank the iron supplements together. It is expected that teachers will educate and accompany students when taking iron tablets before entering class; Providing a Health Report for adolescent girls; Forming Healthy Teenage Ambassadors; and provides funds to buy fruit that can be shared with the students so that when the students consume the iron tablets not feel nauseous